Generic skills: Understanding vocational education and training teacher and student attitudes - Callan, Victor J.; Authority, Australian National Training (National Centre for Vocational Education Research (NCVER), 2003)
« The aim of this project was to find out the attitudes students undertaking vocational education and training (VET) courses and their teachers have about generic skills. Specifically, the project investigated: - the extent to which generic skills are valued by students and VET teachers, and why - how generic skills are being facilitated through VET subjects and courses, and in traineeships and apprenticeships. »
Keywords: compétence; enseignement professionnel